2012
DOI: 10.1155/2012/697489
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box-1 and Endothelial Cell Angiogenic Markers in the Vitreous from Patients with Proliferative Diabetic Retinopathy

Abstract: The aim of this study was to measure the levels of high-mobility group box-1 (HMGB1) in the vitreous fluid from patients with proliferative diabetic retinopathy (PDR) and to correlate its levels with clinical disease activity and the levels of vascular endothelial growth factor (VEGF), the angiogenic cytokine granulocyte-colony-stimulating factor (G-CSF), the endothelial cell angiogenic markers soluble vascular endothelial-cadherin (sVE-cadherin), and soluble endoglin (sEng). Vitreous samples from 36 PDR and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…As mentioned previously, numerous studies have documented marked increases in vitreous VEGF levels in DME and PDR [12][13][14][15][16][17][18][19][20][21]. The rule of vitreous/plasma concentration ≥ 1 certainly applies to VEGF, where levels in DME and retinal tissue surrounding the macula is partially ablated by multiple hemorrhage, proteins from the blood contaminate these vitreal samples PDR vitreous can be many fold those found in plasma [17].…”
Section: Vitreous Levels Of Angiogenesis Factors In Diabetic Retinopathymentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, numerous studies have documented marked increases in vitreous VEGF levels in DME and PDR [12][13][14][15][16][17][18][19][20][21]. The rule of vitreous/plasma concentration ≥ 1 certainly applies to VEGF, where levels in DME and retinal tissue surrounding the macula is partially ablated by multiple hemorrhage, proteins from the blood contaminate these vitreal samples PDR vitreous can be many fold those found in plasma [17].…”
Section: Vitreous Levels Of Angiogenesis Factors In Diabetic Retinopathymentioning
confidence: 99%
“…Additional cytokines and growth factors have been observed to be elevated in the vitreous of DME and PDR patients including: interleukin-1beta (IL-1β) [ [145], granulocyte-colony stimulating factor (G-CSF) [15], macrophage-colony stimulating factor (M-CSF) [89], and platelet factor 4 (PF-4, CXCL4) [21]. However, it is important to consider the how plasma extravasation and hemorrhage may be influencing the inflammatory milieu of the vitreous, especially in PDR patients.…”
Section: Additional Cytokines In Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported increased levels of pro-angiogenic factors and cytokines in the vitreous of DR patients, particularly those with severe diabetic macular edema and PDR [21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…GA has also been shown to bind to and inhibit mitogenic, chemoattractant, and cytokine-like activities of HMGB1 [11] . We demonstrated increased levels of HMGB1 in the vitreous samples from patients with proliferative diabetic retinopathy (PDR) [12] and the in situ localization of the expression of HMGB1 and RAGE in vascular endothelial cells and stromal cells in fibrovascular epiretinal membranes from patients with PDR [13] . Furthermore, we demonstrated that diabetes induced significant upregulation of the expression of HMGB1, RAGE, activated extracellular signal-regulated kinase 1 and 2 (ERK1/2) and activated nuclear factor-κB in the retinas of rats and mice and that intravitreal administration of HMGB1 in normal rats mimics the effect of diabetes [14] .…”
mentioning
confidence: 99%